2021
DOI: 10.1108/ijcma-12-2020-0201
|View full text |Cite
|
Sign up to set email alerts
|

Exploring conflicts between stakeholders in tourism industry. Citizen attitude toward peer-to-peer accommodation platforms

Abstract: Purpose The expansion of online platforms for renting tourist accommodations has given rise to a great deal of controversy in society. Likewise, the arrival of tourists in residential settings has led to a wide range of positive and negative impacts, resulting in conflicts between different stakeholders. The purpose of this paper is to analyze whether there is variation in the perception of the impacts associated with peer-to-peer accommodation platforms among different stakeholders? Additionally, it also seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…One source of conflict is the differing needs and expectations of the local population regarding quality of life [39]. Disputes concern the question of "who has the right to the city" [40].…”
Section: Conflicts Between the Stakeholders Of Tourist Destinationsmentioning
confidence: 99%
“…One source of conflict is the differing needs and expectations of the local population regarding quality of life [39]. Disputes concern the question of "who has the right to the city" [40].…”
Section: Conflicts Between the Stakeholders Of Tourist Destinationsmentioning
confidence: 99%
“…Juan M. Hernández, et al proposed a method based on stepwise geographically weighted regression (GWR), which allows travelers to make accurate decisions based on price and personal needs [18]. Mazur, M. et al analyzed the differences in the attitudes and perceptions of stakeholders towards tourism accommodation platforms and found that stakeholders consider them based on economic impacts, noting that the differences in attitudes exist in the protection of housing [19]. Ye, S. et al proposed a theoretical model of memorability based on the generation of ordinary and extraordinary experiences [20].…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, this has resulted in inconveniences for local communities (Martín et al, 2021), besides debates about its legitimacy (Bort, 2014) and the method of regulation (Cheng, 2016). The growth of this activity relies on benefits for both the tenants and the owners.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation is based on field work carried out in the city of Granada (Spain) in 2018. This city is the Spanish destination that receives most tourists per resident and is one of the main locations of urban-cultural tourism in the country (Martín et al, 2021). According to the National Statistics Institute, it receives more than 3.5 million travellers annually, including tourists staying in rented housing and tourists who do not stay overnight (National Institute of Statistics, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation